About criminal organization and the participation in criminal groups. Can we distinguish between both crimes? - Rodríguez Olave, Giovanna Yahaira (2022)
The worldwide escalation of organized crime in the past years forced States to seek shared solutions to address this phenomenon. This led to the creation of the Palermo Convention in 2000. This treaty compels the States Parties to incorporate in their domestic criminal law the crime of “participation in a criminal organization”. In Perú, this crime is enshrined in article 317 of the Criminal Code. However, due that this crime is related only to the participation in a criminal group dedicated to organized crime, the Peruvian legislation also incorporated in the Criminal Code the crime of “participation in a criminal group” to address the participation in criminal groups that commit common crime. The fundamental issue that these two crimes raise is that the wording of both articles in the Criminal Code is not clear enough to differentiate between the commission of both crimes, which is problematic, because it causes a lack of legal certainty.